2019
DOI: 10.1182/bloodadvances.2019000106
|View full text |Cite
|
Sign up to set email alerts
|

Insights into determinants of spleen injury in sickle cell anemia

Abstract: Spleen dysfunction is central to morbidity and mortality in children with sickle cell anemia (SCA). The initiation and determinants of spleen injury, including acute splenic sequestration (ASS) have not been established. We investigated splenic function longitudinally in a cohort of 57 infants with SCA enrolled at 3 to 6 months of age and followed up to 24 months of age and explored the respective contribution of decreased red blood cell (RBC) deformability and increased RBC adhesion on splenic injury, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…This finding is corroborated by reports from the Middle East, which also showed preservation of spleen function into adulthood among patients with SCD with splenomegaly 73,92 . However, in contrast reports from the West suggest loss of splenic function in most patients by the age of 2 years 6,93,94 . In view of these conflicting data across regions, further studies are needed to fill this gap in knowledge regarding the age and prevalence of splenic dysfunction in patients with SCD in Africa.…”
Section: Discussionsupporting
confidence: 67%
“…This finding is corroborated by reports from the Middle East, which also showed preservation of spleen function into adulthood among patients with SCD with splenomegaly 73,92 . However, in contrast reports from the West suggest loss of splenic function in most patients by the age of 2 years 6,93,94 . In view of these conflicting data across regions, further studies are needed to fill this gap in knowledge regarding the age and prevalence of splenic dysfunction in patients with SCD in Africa.…”
Section: Discussionsupporting
confidence: 67%
“…The red pulp is instead congested by RBCs, and congestion is probably caused by markedly impaired deformability and increased adhesion properties of sickle RBCs. These abnormalities play a key role in progressive spleen damage and loss of function [3].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study using 99 m Technetium (Tc) sulfur-colloid liver–spleen scan to evaluate the phagocytic ability of splenic macrophages in 193 infants aged 8–18 months found that loss of splenic function began before 12 months of age in 86% of infants [4]. Another study, investigating the mechanical filtration ability of the spleen by using 99 m Tc heated RBC scintigraphy in a cohort of 57 infants with sickle cell anemia, showed that in 32% and 50% of infants, splenic function was decreased at 6 and 18 months of age, respectively [3]. The age varies for irreversible fibrosis of the spleen (a loss also referred to as autosplenectomy), and changes have been described over time, likely due to improved supportive care and the use of acute and chronic transfusion therapy [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring splenic function is of clinical interest in multiple conditions, including sickle cell anaemia (SCA) ( Brousse et al, 2014 ). In SCA, spleen damage occurs in early childhood, leading to loss of function within the first years of life ( Pearson et al, 1969 ; Pearson et al, 1985 ; El Hoss et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%